(untitled) (Journal of Renal and Hepatic Disorders, 2021)
The clinical features of corona virus disease 2019 (COVID-19) are variable, but the majority of patients experience mild flu-like symptoms. The cases of severe disease include complications such as progressive pneumonia, acute kidney injury (AKI), multi-organ failure, and even death. This paper explores the association between COVID-19 and its effect on multiple organ systems and how the subsequent treatment of this dis-ease can itself lead to morbidity and mortality. We present a case that emphasizes the life-threatening gastrointestinal complications associated with the treatment of AKI in a patient with COVID-19. We conclude that the patients whose treatment regimens utilize medical resins should be closely monitored for gastrointestinal complications so as to mitigate the known adverse effects associated with these drugs, such as colonic mucosal ulceration, perforation, or even death.